In vitro elution of amikacin, cefazolin, gentamicin, ampicillin/sulbactam, and meropenem from a commercially available calcium sulfate delivery kit - Maxwell, Elizabeth A.; Howell, Taylor; Mester, Rachel; Bennett, R. Avery; Cruz-Espindola, Crisanta; Boothe, Dawn (Frontiers in Veterinary Science, 2024)
Introduction The use of implantable antibiotic beads has become a frequent treatment modality for the management of surgical site infections in human and veterinary medicine. The objective of this study is to describe the elution kinetics of five antibiotics from a commercially available calcium sulfate antibiotic delivery kit. A secondary goal was to compare elution concentrations with minimal inhibitory concentrations (MIC) for commonly encountered bacteria from the University of Florida’s veterinary microbiology laboratory database. Methods Calcium sulfate powder was combined with amikacin, cefazolin, gentamicin, ampicillin/sulbactam, and meropenem. Triplicates of three antibiotic-loaded beads were immersed in 5 mL of phosphate-buffered saline (PBS) and kept at 37°C under constant agitation. Antibiotic-conditioned PBS was sampled at 14 time points from 1-h to 30 days and analyzed by liquid chromatography to determine the antibiotic concentration. Results All beads eluted concentrations of antibiotics for the 30-day sampling period, except for ampicillin/sulbactam, with the most antibiotics being eluted within the first week. The concentration of antibiotics within the eluent within the first 3–9 days (3- and 5-mm beads, respectively) was greater than the MIC of common isolates. The 5 mm bead samples were superior in maintaining higher concentrations for a longer period, compared to the 3-mm beads. Discussion CSH beads eluted antibiotics over the 30-day course of the study. Most of the antibiotic elution occurred within the first week and was maintained above the MIC of commonly encountered isolates. This information may be useful for clinical decision making for treatment of local infections encountered in practice.